1976
DOI: 10.1007/bf00219145
|View full text |Cite
|
Sign up to set email alerts
|

Influence of castration followed by administration of LH-RH on the ultrastructure of rat pinealocytes

Abstract: The ultrastructure of adult male rat pinealocytes was studied after orchidectomy and orchidectomy followed by LH-RH administration. Castration causes an increased development of the rough endoplasmic reticulum and the Golgi apparatus as well as an increase in the number of lipid droplets and lysosomes. The changes after orchidectomy followed by LH-RH administration were more marked than after castration alone. The ultrastructural features observed after castration can be interpreted as a morphological equivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1
1

Year Published

1977
1977
1992
1992

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 34 publications
3
17
1
1
Order By: Relevance
“…In the mole-rat this process occurs only in pineatocytes of population It. Moreover, Karasek et aL (1976) recently observed a general increase of synthetic activity of rat pinealocytes aPcer castration. These authors especially observed the formation, by the cisterns of the granular endoplasmic reticulum, of vacuoles containing flocculent material of moderate electron density, these vacuoles being released into the extracetlular space.…”
Section: Discussionmentioning
confidence: 99%
“…In the mole-rat this process occurs only in pineatocytes of population It. Moreover, Karasek et aL (1976) recently observed a general increase of synthetic activity of rat pinealocytes aPcer castration. These authors especially observed the formation, by the cisterns of the granular endoplasmic reticulum, of vacuoles containing flocculent material of moderate electron density, these vacuoles being released into the extracetlular space.…”
Section: Discussionmentioning
confidence: 99%
“…On the eleventh day after surgery, rats of groups 1 (HYPx + SAL) and 3 (SH-HYPx + SAL) received s.c. injections of 0.5 ml 0.9 % NaCl (SAL) at 2200 h, followed by a second injection on the next day at 0800 h. (Weibel, 1979 (Karasek, 1981 ;Karasek et aL, 1982). The Golgi apparatus, DCV, GER and VFC are believed to be involved in the secretory processes of the pinealocytes (Pevet, 1979 ;Karasek, 19811, whereas the LYS and LD probably are involved in general cell metabolism (Quay, 19741, although a role of LYS in secretory processes in the pinealocytes also has been suggested (Karasek et al, 1976 ;Karasek, 19811. The results of the present study, together with the known influence of the pineal gland on the hypophysis, support the existence of a reciprocal hypophysialpineal relationship. Both PRL and HYPx influence the ultrastructure of the pinealocytes.…”
Section: Methodsmentioning
confidence: 99%
“…The first process (neurosecretory-like) is characterized by the formation of DCV by the Golgi apparatus, while the second process (ependymal-like) is characterized by a peculiar activity in the granular endoplasmic reticulum. In rat pinealocytes, this activity is characterized by the formation of VFC by the cisternae of the GER (Karasek et al, 1976 ;Pevet and Karasek, 1977 ;Karasek, 19811. Although the exact chemical nature of the substances present in production of a proteinaceous material (Pevet, 1979 (Karasek et al, 1982 …”
Section: Methodsmentioning
confidence: 99%
“…These findings are, at least, suggestive of some relationship between their presence, the functional state of this type of pinealocyte and the functional state of the sex organs. In castrated rats, the endoplasmic reticulum in such pinealocytes has been shown to produce vacuoles containing moderately dense material which is released into intercellular spaces (Karasek et al, 1976) Similar vacuoles the origin of which could, however, not be established exactly, have been demonstrated in hedgehog pinealocytes at the beginning of the physiological phase of quiescence (Pevet and Saboureau, 1973) and also when such a quiescence was experimentally induced (Pevet and Saboureau, 1974). Not in all mammalian pineals two populations of pinealocytes showing clearly the different characteristics mentioned can be distinguished.…”
mentioning
confidence: 99%